Highly Selective Hg (II) Ion Detection Based on Linear Blue-Shift of the Maximum Absorption Wavelength of Silver Nanoparticles - Li Ping Wu; Hua Wen Zhao; Zhu Hong Qin; Xian Ying Zhao; Wen Dan Pu (Journal of Analytical Methods in Chemistry)
A new method of detecting Hg (II) ion with silver nanoparticles (AgNPs) is developed in this contribution. When Hg (II) ions were added into AgNPs solution, the solution displayed rapid color change and blue shift of the maximum absorption wavelength (Δλ), which was in proportion to the Hg (II) ion concentration over the range of 2.0 × 10−7–6.0 × 10−6 mol/L, with detection limit (3σ) of 6.6 × 10−9 mol/L. Under the same experimental conditions, other metal ions did not interfere. Thus, we propose a rapid, simple and highly selective method for detecting Hg (II) ion.